2018
DOI: 10.1038/s41598-018-26080-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and miRNA analyses of the response to Corynespora cassiicola in cucumber

Abstract: Cucumber (Cucumis sativus L.) target leaf spot (TLS), which is caused by the fungus Corynespora cassiicola (C. cassiicola), seriously endangers the production of cucumber. In this assay, we performed comprehensive sequencing of the transcriptome and microRNAs (miRNAs) of a resistant cucumber (Jinyou 38) during C. cassiicola inoculation using the Illumina NextSeq 500 platform. The possible genes related to the response to C. cassiicola were associated with plant hormones, transcription factors, primary metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 72 publications
1
35
0
Order By: Relevance
“…Plant miRNAs, small noncoding molecules, have numerous biological functions that may be involved in the regulation of plant growth and development and environmental stress responses. Some plant miRNAs can downregulate the expression of target genes to get through the demands of growth and environmental stress [49]. The quantitative real-time reverse transcriptase polymerase chain reaction (qRT-PCR) technique is widely utilized in molecular biology investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Plant miRNAs, small noncoding molecules, have numerous biological functions that may be involved in the regulation of plant growth and development and environmental stress responses. Some plant miRNAs can downregulate the expression of target genes to get through the demands of growth and environmental stress [49]. The quantitative real-time reverse transcriptase polymerase chain reaction (qRT-PCR) technique is widely utilized in molecular biology investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, transcriptome and isobaric tags for relative absolute quantification (iTRAQ) analyses identified two genes, CsMLO1 and CsMLO2 , in cucumber that are involved in the response to Corynespora cassiicola . Proteins/genes that are mainly involved in the defense response and oxidative stress and calcium signaling pathways during C. cassiicola infection have been identified in cucumber [13,14]. In addition, our research finds that the functions of CsMLO1 and CsMLO2 in C. cassiicola infection act as negative modulators to enhance the expression of reactive oxygen species (ROS)-related genes and defense-related genes for improved cucumber disease resistance [15].…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic analyses of transgenic cucumber cotyledons inoculated with C. cassiicola revealed that transient overexpression of either CsMLO1 or CsMLO2 in cucumber cotyledons reduced resistance to C. cassiicola , whereas silencing of either CsMLO1 or CsMLO2 enhanced resistance to C. cassiicola . [13,14]. In addition, significant changes of calmodulin involved in calcium signaling were detected after treatment with C. cassiicola by iTRAQ analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research found that secondary metabolism plays an important role in cucumber in response to C. cassiicola infection (Wang et al, 2018). Based on previous study, two known miRNAs and two novel miRNAs with their targets were selected, as they may be involved in enhanced C. cassiicola resistance in cucumber (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, high-throughput sequencing was performed to investigate the differentially expressed miRNAs in cucumber inoculated with C. cassiicola , including two known miRNAs (miR164d and miR396b) and two novel miRNAs (Novel-miR1 and Novel-miR7) (Wang et al, 2018). Based on the analyses of target genes function, we believe that these miRNAs play important roles in the interaction between cucumber and C. cassiicola .…”
Section: Introductionmentioning
confidence: 99%